The Effect of Active, Creative, Effective, and Enjoyable Learning Models on the Fourth-Grade Students’ Learning Outcomes - Rika Olimina Malau; Patri Janson Silaban; Rebekah Kairani Sembiring; Bogor Lumbanraja; Rumiris Lumban Gaol (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines the impact of the PAKEM (Active, Creative, Effective, and Joyful Learning) instructional model on students’ learning outcomes in the thematic unit “The Area Where I Live” among fourth-grade students at SD Negeri 097795 Perasmian during the 2022/2023 academic year. Employing a quantitative research design, the study involved a population of 132 students drawn from grades I to VI. A purposive sampling technique was applied to select 30 students from grade IV as the research sample. Data analysis reveals that students taught using the PAKEM learning model achieved learning outcomes categorized as very good, with a mean score of 85.13. The correlation analysis indicates a strong positive relationship between the use of the PAKEM model and student learning outcomes, as evidenced by an obtained correlation coefficient of 0.841, which exceeds the critical value (rₜₐᵦₗₑ = 0.361). This result confirms the acceptance of the alternative hypothesis. Furthermore, the t-test analysis demonstrates a statistically significant effect, with a calculated t-value of 8.215 surpassing the critical t-value of 2.048. These findings provide empirical evidence that the PAKEM learning model exerts a significant and positive influence on students’ learning outcomes. Consequently, the study underscores the effectiveness of student-centered and active learning approaches in enhancing thematic learning achievement at the elementary school level.